Dryinidae of the Afrotropical region (Hymenoptera, Chrysidoidea) - Olmi, Massimo; Copeland, Robert S.; van Noort, Simon (Zootaxa, 2019)
An updated revision of Afrotropical Dryinidae is presented. Nine subfamilies, 23 genera and 430 species (including 60 new species) are treated. Six new species-level synonymies and three new combinations are proposed. Descriptions, geographic distribution, known hosts, natural enemies and type material of each species are presented, together with illustrations of the main morphological characters and keys to the subfamilies, genera and species. A complete list of references concerning the Afrotropical Dryinidae and their hosts is provided. The following new species are described: Anteon ambrense, sp. nov. (Madagascar), Anteon beankanum, sp. nov. (Madagascar), Anteon elongatum, sp. nov. (Madagascar), Anteon hoekense, sp. nov. (South Africa), Anteon mabibiense, sp. nov. (South Africa), Anteon majunganum, sp. nov. (Madagascar), Anteon malagasy, sp. nov. (Madagascar), Anteon musmani, sp. nov. (Kenya), Anteon nigropictum, sp. nov. (South Africa), Anteon nimbense, sp. nov. (Guinea), Anteon pseudohova, sp. nov. (Madagascar), Anteon sakalavense, sp. nov. (Madagascar), Anteon tulearense, sp. nov. (Kenya, Madagascar), Aphelopus sequeirai, sp. nov. (Kenya), Apoaphelopus fisheri, sp. nov. (Madagascar), Apoaphelopus wallacei, sp. nov. (Kenya), Bocchus forestalis, sp. nov. (Madagascar), Bocchus granulatus, sp. nov. (South Africa), Bocchus harinhalai, sp. nov. (Madagascar), Bocchus nigroflavus, sp. nov. (Madagascar), Bocchus parkeri, sp. nov. (Madagascar), Bocchus ruvidus, sp. nov. (Madagascar), Conganteon hawleyi, sp. nov. (Kenya), Conganteon sensitivum, sp. nov. (Madagascar), Crovettia afra, sp. nov. (Kenya, Madagascar), Deinodryinus ambrensis, sp. nov. (Madagascar), Deinodryinus granulatus, sp. nov. (South Africa), Deinodryinus nigropictus, sp. nov. (South Africa), Deinodryinus piceus, sp. nov. (Madagascar), Dryinus bellicosus, sp. nov. (Madagascar), Dryinus dentatiforceps, sp. nov. (South Africa), Dryinus erenianus, sp. nov. (Ivory Coast), Dryinus milleri, sp. nov. (Kenya), Dryinus mobotensis, sp. nov. (Madagascar), Dryinus nigrithorax, sp. nov. (Ivory Coast), Dryinus teres, sp. nov. (Madagascar), Dryinus tulearensis, sp. nov. (Madagascar), Dryinus whittleorum, sp. nov. (Kenya), Gonatopus avontuurensis, sp. nov. (South Africa), Gonatopus bellicosus, sp. nov. (Madagascar), Gonatopus comorensis, sp. nov. (Union of the Comoros), Gonatopus costalis, sp. nov. (South Africa), Gonatopus flavotestaceus, sp. nov. (Madagascar), Gonatopus gumovskyi, sp. nov. (Democratic Republic of the Congo), Gonatopus hantamensis, sp. nov. (South Africa), Gonatopus harinhalai, sp. nov. (Madagascar), Gonatopus karooensis, sp. nov. (South Africa), Gonatopus koebergensis, sp. nov. (South Africa), Gonatopus marojejyanus, sp. nov. (Madagascar), Gonatopus minutus, sp. nov. (Madagascar), Gonatopus nigropictus, sp. nov. (South Africa), Gonatopus ranomafanensis, sp. nov. (Madagascar), Gonatopus robertsoni, sp. nov. (South Africa), Gonatopus rugithorax, sp. nov. (South Africa), Gonatopus scholtzi, sp. nov. (South Africa), Gonatopus wikstrandae, sp. nov. (Kenya), Lonchodryinus madagascolus, sp. nov. (Madagascar), Madecadryinus ranomafanensis, sp. nov. (Madagascar), Neodryinus bimaculatus, sp. nov. (Madagascar), Neodryinus keleboensis, sp. nov. (Democratic Republic of the Congo). The ♀ of Deinodryinus danielssoni Olmi, 1998, is described for the first time. The following new synonymies are presented: Anteon fiorii Olmi, 1984 (=A. proteicolum Olmi, 2006, syn. nov.); Anteon madagascolum (Benoit, 1954) (=Anteon brooksi Olmi, 2003, syn. nov.); Anteon zairense Benoit, 1951 (=A. terminale Olmi, 2007, syn. nov.); Aphelopus incisus Olmi, 1984 (=A. himyarita Olmi & van Harten, 2006, syn. nov.); Bocchus watshami Olmi, 1987 (=Bocchus simoni Olmi, 2005, syn. nov.); Dryinus ugandanus Olmi, 1984 (=Dryinus constantiae Olmi, 2006, syn. nov.). The following new combinations are presented: Dryinus luweli (Benoit, 1951) new comb. in place of Lestodryinus luweli Benoit, 1951; Gonatopus africanus (Benoit, 1951) new comb. in place of Aphelopus africanus Benoit, 1951; Gonatopus ghanensis (Olmi, 1987) new comb. in place of Pseudogonatopus ghanensis Olmi, 1987. Gynander specimens of Deinodryinus rusticus Olmi, 2004 and Deinodryinus steineri Olmi, 1994 are described (first gynander specimens of Dryinidae from the Afrotropical region). The authors provide well-illustrated identification keys to all species of Afrotropical Dryinidae. Online Lucid Phoenix and Lucid matrix interactive keys are provided at http://www.waspweb.org.